Towards developing a framework on happiness and productivity among personnel in institution of higher learning - Mazuki, Raidah; Abu Samah, Asnarulkhadi; Omar, Siti Zobidah; Zawawi, Dahlia; Idris, Khairuddin; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Dahalan, Dzuhailmi; Kamaruddin, Nurani; Kamarudin, Nurul Akhtar; Mohamed, Nor Aini (Human Resource Management Academic Research Society, 2017)
Happiness undeniably facilitates staff’s productivity in the workplace. Productivity could be changed by the developments in the level of knowledge, income or the technology innovation. The focus of this paper is to ascertain the prospective factors that will influence the level of productivity among personnel in Institution in Higher Learning. Numerous factors were identified and it will be a useful input for future researchers that are seeking directions to investigate the contributing factors of productivity in a higher learning institution.